Evaluating the hip-flask defence in subjects with alcohol on board: An experimental study. (January 2019) - Kronstrand, Christoffer; Nilsson, Gunnel; Chermà, Maria D.; Ahlner, Johan; Kugelberg, Fredrik C.; Kronstrand, Robert
Highlights: The UAC/BAC ratio was less sensitive to detect a recent intake in subjects with alcohol on board. Two consecutive urine samples provided good evidence for investigating the hip-flask defence. Small or moderate amounts of recently taken ethanol can go undetected. Abstract: Driving under the influence of alcohol is a major problem for traffic-safety and a popular defence argument is alleged consumption after driving, commonly referred to as the hip-flask defence. Forensic toxicologists are often called as expert witnesses in drinking and driving cases where the suspect has claimed the hip-flask defence, to assess the credibility of the explanation. Several approaches to help the expert have been introduced but the scientific data used to support or challenge this is solely based on data from controlled single doses of ethanol administered during a short time and in abstinent subjects. In reality, we believe that even in drinking after driving cases, the subject many times has alcohol on board at time of the hip-flask drink. This questions the applicability of the data used as basis to investigate the hip-flask defence. To fill this knowledge gap, we aimed to investigate how blood and urine ethanol kinetics vary after an initial drinking session of beer and then a subsequent hip-flask drink of three different doses of whiskey. Fifteen subjects participated in the study and each provided 10 urine samples and 17 blood samples over 7 h. The initial drink was 0.51 g ethanol/kg and the second was either 0.25, 0.51, or 0.85 g/kg. Our data suggested that the difference between the ethanol concentrations in two consecutive urine samples is a more sensitive parameter than the ratio between urine and blood alcohol to detect a recent intake when ethanol from previous intakes are already present in the body. Twelve subjects presented results that fully supported a recent intake using the criteria developed from a single intake of ethanol. Three subjects showed unexpected results that did not fully support a recent intake. We conclude that data from one blood sample and two urine samples provide good evidence for investigating the hip-flask defence even if alcohol was on board at the time of the hip-flask drink.